Molecular characterization of aflatoxigenic aspergilli-contaminated poultry and animal feedstuff samples from the western region of Saudi Arabia - YOUSSUF A. GHERBAWY; YASSMIN M. SHEBANY; HELAL F. ALHARTHY (Chiriotti Editori, 2016)
The aflatoxigenic abilities of 64 and 17 isolates of Aspergillus flavus and A. parasiticus isolated from poultry and animal feedstuff samples collected from the western region of Saudi Arabia were studied. Thirty-three (51.6%) and 13 (76.5%) isolates of A. flavus and A. parasiticus, respectively, were aflatoxigenic. The ranges of aflatoxins in A. flavus and A. parasiticus isolates were 4.4-110 and 143.6-271.3 ppm (μg/g), respectively. A. parasiticus isolates generally produced a greater amount of aflatoxins than A. flavus. A. flavus isolates from poultry, cattle, and camel and cattle feeds produced aflatoxin amounts in the range 5.7-110, 4.4-19.0, and 7.0-28.5 ppm, respectively. From poultry feedstuff samples, A. parasiticus produced aflatoxins in the range 212.5-232.4 ppm. Some aflatoxin biosynthesis genes (aflR, omt-1, ver-1, and nor-1) were detected with variable frequencies in all A. flavus and A. parasiticus isolates. The genetic diversity among 64 isolates of A. flavus using internal transcribed spacer sequence results and the amplification of some aflatoxin biosynthesis genes revealed that the investigated isolates showed high heterogeneity.